The Effect of Animation-Guided Mindfulness Meditation on the Promotion of Creativity, Flow and Affect - Chen, Hao; Liu, Chao; Zhou, Fang; Chiang, Chao-Hung; Chen, Yi-Lang; Wu, Kan; Huang, Ding-Hau; Liu, Chia-Yih; Chiou, Wen-Ko (Frontiers in Psychology, 2022)
Creativity plays an important role in People's Daily life, study and work, and is of great significance to the progress of society and the improvement of life quality. However, there are few studies on the relationship between mindfulness and creativity, and the results of the few studies are controversial, and the mechanism between mindfulness and creativity is still uncertain. Animation has been shown by many studies to help improve cognition and is often used as a guiding and illustrative tool. Using animation as the guiding carrier of meditation is convenient and easy to accept. Therefore, this study adopted the intervention method of animation-guided meditation, aiming to explore :(1) the effect of animation-guided meditation on enhancing creativity; (2) the role of flow and emotion in the influence of mindfulness on creativity. We advertised recruitment through the internal network of a creative industrial park, and the final 95 eligible participants were divided into two groups: animation (n = 48) and audio (n = 47) guided meditation. The animation group was given an animated meditation intervention, and the audio group was given an audio meditation intervention, both interventions were performed 3 times a week and last for 8 weeks. Results: (1) Animation-guided meditation significantly increased participants' mindfulness and creativity levels and significantly reduced their cognitive load compared to audio-guided meditation. (2) Mindfulness has a significant direct effect on creativity, and significant indirect effects on creativity in which flow and PA acts as the mediating variable and has a significant partial mediating effect. Conclusions: (1) Mindfulness, flow, and PA all helped to improve the subjects' work creativity. In addition to the direct positive impact of mindfulness on creativity, mindfulness can also have an indirect positive impact on creativity through flow and PA, and flow and PA play a partial mediating role. (2) Compared with static text, graphics and audio, animation can significantly reduce cognitive load and help improve users' cognitive ability, which is more suitable for the guidance and illustration materials of mindfulness meditation to enhance the effect of meditation.